Under which King, Bezonian? Literary Studies between Hermeneutics and Quantification - Moretti, Franco (Porównania, 2020)
What is the relationship between the quantitative literary history of the past twenty years and the older hermeneutic tradition? Answers have typically been of two kinds: for many in the interpretive camp, the two approaches are incompatible, and the newer one has little or no critical value; for most quantitative researchers, they are instead perfectly compatible, and in fact complementary. Here, I will propose a third possibility, that will emerge step by step from a comparison of how the two strategies work. How they work, literally; in the conviction that practices – what we learn to do by doing, by professional habit, and often without being fully aware of what we are doing – have frequently larger theoretical implications than theoretical statements themselves. In other words: understanding what a research paradigm does, rather than what it declares it wants to do. This is the plan.